EFFECT WORK LIFE BALANCE, WORKLOAD AND ROLE CONFLICT ON WORK STRESS FOR MEMBERS OF KERINCI POLICE CRIMINAL INVESTIGATION - Muslikan, Ahmad; Ali, Helmi (STIE Bangkinang Publishing, 2022)
This study aims to determine the effect of life balance, workload and role conflict on work stress for members of the Kerinci Police Criminal Investigation Unit. The sample is 40 members of the Kerinci Criminal Investigation Unit. The research method is descriptive and associative research by drawing conclusions using quantitative methods. The results of the study partially affect work-life balance on work stress. Workload has no effect on work stress. Role Conflict has no effect on work stress and simultaneously the influence of Life Balance, Workload, and Role Conflict have a positive and significant effect on work stress on members of the Kerinci Criminal Investigation Unit.